Incidence of caesarean delivery after induction of labour in nulliparous women with unfavorable bishops score at tertiary care centre - Patidar, B. L.; Saini, Monika; Gupta, Vinita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Induction of labour means initiation of uterine contractions before onset of spontaneous labour to achieve vaginal delivery, because birth by caesarean delivery is more hazardous than vaginal delivery. Prostaglandins are used in management of Labour and are introduced as agent for induction of Labour. Nulliparous women are more likely to undergo induction of labour and are at a higher risk of caesarean delivery after induction of labour, as compared to multiparous women. Objective of current study was to determine the incidence of caesarean delivery in nulliparous women with unfavourable bishop’s score when induced with dinoprostone gel. Methods: This Hospital based Prospective interventional Study was conducted among 200 nulliparous women of 18-35 years of age with a singleton pregnancy with cephalic presentation at 37-42 weeks with unfavorable bishop score (≤5) and reactive fetal heart rate pattern with no contraindication of vaginal delivery. Results: In our study of 200 participants majority were in the age group of 18-25 years (86%), with period of gestation 40 weeks (45.5%), most common indication of induction was postdated pregnancy (46.5%). Incidence of caesarean delivery was 28.5% and most common indication of caesarean was secondary arrest of labour in 46.5%. Conclusions: The current study concluded that incidence of LSCS was found to be 28.5%. Duration of induction and dose of dinoprostone had positive association with increased incidence of LSCS.